Motor outcome after perinatal stroke and early prediction of unilateral spastic cerebral palsy. (November 2020) - Pascal, Aurelie; Govaert, Paul; Ortibus, Els; Naulaers, Gunnar; Lars, Adde; Fjørtoft, Torill; Oostra, Ann; Zecic, Aleksandra; Cools, Filip; Cloet, Eva; Casaer, Alexandra; Cornette, Luc; et al.
Abstract: Background: Unilateral spastic cerebral palsy (USCP) occurs in 30%–68% of infants with perinatal stroke. Early detection of USCP is essential for referring infants to early intervention. The aims of this study were to report motor outcomes after perinatal stroke, and to determine the predictive value of the General Movements Assessment (GMA) and Hand Assessment for Infants (HAI) for detection of USCP. Materials and methods: This was a prospective observational study involving infants with perinatal stroke. GMA was conducted between 10 and 15 weeks post term-age (PTA). The HAI was performed between 3 and 5 months PTA. Motor outcome was collected between 12 and 36 months PTA. Results: The sample consisted of 46 infants. Fifteen children (32.6%) were diagnosed with CP, two children with bilateral CP and 13 with USCP. Abnormal GMA had a sensitivity of 85% (95% confidence interval [CI] 55–98%) and a specificity of 52% (95% CI 33–71%) to predict USCP. When asymmetrically presented FMs were also considered as abnormal, sensitivity increased to 100%, hence the specificity declined to 43%. A HAI asymmetry index cut-off of 23, had both a sensitivity and a specificity of 100% to detect USCP. Conclusion: Using GMA and HAI can enable prediction of USCP before the age of 5 months in infants with perinatal stroke. Nevertheless, GMA must be interpreted with caution in this particular population. The HAI was found to be a very accurate screening tool for early detection of asymmetry and prediction of USCP. Highlights: One-third of the infants with perinatal stroke developed cerebral palsy (CP). General movement assessment must be interpreted cautiously after perinatal stroke. The Hand Assessment for Infants is highly predictive for unilateral CP.